Creative watercolor : new ways to express yourself - Moses, Marcia (New York, NY Sterling Publishing Company, 2005)
Marcia Moses, whose award-winning Easy Watercolor taught beginners the basic skills of the art, now takes painters the next step in their creative journey. These lessons are meant for intermediates, and they're as illuminating and exquisitely illustrated as the ones in her first volume. After reviewing the fundamentals, Moses delves deeply into color (understanding its properties, creating harmony and conflict, mixing exciting hues); techniques in action, from backgrounds and texture to layering, shading, and brushstrokes; and painting with feeling. See how to add figures and set them in motion. Capture nature, including moody skies and watery landscapes. Put all the elements together for a satisfying finished work. Above all, Moses gives developing painters the gift of understanding how to use their imaginations--the key to artistic success. A Selection of the Crafters Choice Book Club.
Introduction 00
CT:Getting Started: Reviewing the Fundamentals 00
An Artist's Tools 00
The Brush & Its Properties 00
Composition & Design 00
Easy Drawing: Breaking Down a Shape 00
Dealing with Perspective 00
CT:Color 00
Color Harmony & Conflict 00
Repeating Colors 00
Pen and Ink 00
Glazing & Layering Color 00
Mixing Exciting Colors 00
Properties of Color 00
Amazing Color 00
Warming Up & Cooling Down 00
Color Combinations 00
The Color of White 00
CT:Techniques in Action 00
Backgrounds 00
Giving Layered Backgrounds Texture 00
Texture That Adds Dimension 00
Capturing Nature 00
Painting Fences & Walls 00
Effective Brush Strokes 00
Getting an Edge 00
Painting Light to Dark 00
Painting Water Droplets 00
Adding Figures 00
Putting Figures in Motion 00
CT:Positive Approaches to Watercolor 00
Painting with Feeling 00
Solving Problems 00
Controlling Dominance 00
Taking a Break from a Painting 00
Finishing a Painting 00
CT:Putting It All Together 000
Moody Skies 000
Painting Water 000
A Foggy Scene 000
Snow Scenes 000
Cityscapes 000
Boats That Float 000
Window Treatments 000
Pots & Jars 000
Flowers 000
CT:Watercolor Students' Gallery 000
For Students 000
Epilogue 000
Acknowledgments 000
Glossary 000
Metric Equivalents 000
Index to Watercolor Paintings 000
Index 000
Includes indexes
Keywords: Watercolor painting - Technique